Pengaruh Keberadaan Institusi Perwakilan Perdagangan di Luar Negeri terhadap Kinerja Ekspor Nonmigas Indonesia - Sunaryo, Sanny (Jurnal Kebijakan Ekonomi, 2020)
Indonesia has two trade representative institutions abroad, namely: Trade Attaché in 23 states and the Indonesian Trade Promotion Centre (ITPC) in 18 countries. Both institutions have a duty to improve the Indonesian non-oil exports. The study aims to look at the effectiveness of the budget ITPC and Trade Attaché of the Indonesian non-oil export performance in 2008-2014 in thirty countries. Model estimation is Random Effect and using panel data. The results showed that an increase of 1% of the budget ITPC and Trade Attaché of Indonesian non-oil and gas exports will increase in the following year by 0.027% and 0.109%.